The CSL proteins, versatile transcription factors and context dependent corepressors of the notch signaling pathway. - Contreras-Cornejo, H.; Saucedo-Correa, G.; Oviedo-Boyso, J.; Valdez-Alarcón, J.J.; Baizabal-Aguirre, V.M.; Cajero-Juárez, M.; Bravo-Patiño, A. (Cell Division, 2016)
The Notch signaling pathway is a reiteratively used cell to cell communication pathway that triggers pleiotropic effects. The correct regulation of the pathway permits the efficient regulation of genes involved in cell fate decision throughout development. This activity relies notably on the CSL proteins, (an acronym for CBF-1/RBPJ-? in Homo sapiens/Mus musculus respectively, Suppressor of Hairless in Drosophila melanogaster, Lag-1 in Caenorhabditis elegans) which is the unique transcription factor and DNA binding protein involved in this pathway. The CSL proteins have the capacity to recruit activation or repression complexes according to the cellular context. The aim of this review is to describe the different co-repressor proteins that interact directly with CSL proteins to form repression complexes thereby regulating the Notch signaling pathway in animal cells to give insights into the paralogous evolution of these co-repressors in higher eumetazoans and their subsequent effects at developmental processes.